The Utilization of Sociometric Tests in Identifying School Integration Challenges Among Students with Immigrant Parents. - Oprea Bobocea, Daniela (Technium Social Sciences Journal, 2024)
The purpose of this study is to investigate how sociometric relationships are configured within the primary and secondary school group that have immigrant parents. The analysis of the specialized literature was carried out based on clear selection criteria, both chronologically and of the variables. Statistical analyses, including correlations and frequency calculations, were conducted for the research variables. The study also clarifies certain procedural aspects in the application of sociometric tests. Our study included four school groups, two with 4th-grade students and two with pre-adolescent high school students. Parental emigration is a phenomenon that can have significant negative effects on the school integration of children who are left behind. They may experience emotional stress and anxiety that can affect their school performance. Some may also face financial difficulties, resulting in material shortages necessary to participate in school activities. The overload of tasks and household responsibilities can lead to their stigmatization in school groups. Our study examined three dimensions of school integration: partnership in work activities, participation in leisure time activities, and leadership within the group. The results of the research indicate a poor sociometric positioning for the children of emigrants, who are often rejected by the group for work activities, ignored in terms of spending free time, and overlooked for leadership roles within the group. Even if there are situations where some of them gain followers, they are also among the students rejected by the group. Most of them are ignored or rejected by the more socially prominent students in the class,